The aortic root in repaired tetralogy of Fallot: Serial measurements and impact of losartan treatment. (1st March 2021) - Woudstra, O.I.; Ghanam, A.; Vliegen, H.W.; van Dijk, A.P.J.; van Melle, J.P.; Groenink, M.; Meijboom, F.J.; Post, M.C.; Mulder, B.J.M.; Bouma, B.J.; Bokma, J.P.
Abstract: Background: Aortic root dilatation is common in adults with repaired tetralogy of Fallot (rTOF) and might lead to aortic dissection. However, little is known on progression of aortic dilatation and the effect of pharmaceutical treatment. This study aims to determine factors associated with aortic growth and investigate effects of losartan. Methods and results: We performed a prespecified analysis from the 1:1 randomized, double-blind REDEFINE trial. Aortic root diameters were measured at baseline and after 2.0 ± 0.3 years of follow-up using cardiovascular magnetic resonance (CMR) imaging. A total of 66 patients were included (68% men, age 40 ± 12 years, baseline aortic root 37 ± 6 mm, 32% aortic dilatation (>40 mm)). There was a trend towards slow aortic root growth (+0.6 ± 2.3 mm after two years, p = 0.06) ( n = 60). LV stroke volume was the only factor associated with both a larger baseline aortic root (β: 0.09 mm/ml (95% C.I.:0.02, 0.15), p = 0.010) and with aortic growth during follow-up (β: 0.04 mm/ml (95% C.I.:0.005, 0.066), p = 0.024), after correction for age, sex, and body surface area using linear regression analysis. No treatment effect of losartan was found ( p = 0.17). Conclusions: Aortic root dilatation was present in about one-third of rTOF patients. A larger LV stroke volume was associated with both a larger baseline aortic root and ongoing growth. Our findings provide no arguments for lower aortic diameter thresholds for prophylactic surgery compared to the general population.